Helium permeation through mixed matrix membranes based on polyimides and silicalite-1 - Fryčová, Marie; Sysel, Petr; Hrabánek, Pavel; Kočiřík, Milan; Brabec, Libor; Zikánová, Arlette; Bernauer, Bohumil; Čapek, Pavel Pavel; Hejtmánek, Vladimír (Diffusion Fundamentals, 2009)
Mixed matrix membranes based on modified polyimides and silicalite-1 were prepared and studied. The novel preparation approach consists in improvement of the interfacial adhesion by employment of the coupling agent 3-aminopropyltriethoxysilane in such a way which leads to forming of chemical bonds between polyimide and silicalite-1. Firstly polyimide chains were endcapped by this agent which subsequently enabled their reaction with groups naturally present on silicalite-1 surface. Membranes with silicalite-1 content up to 60 wt. % were prepared and characterized by SEM, light microscopy and permeation of gases, prevailingly of He. The accessibility of sililicalite-1 pores prior to embedding and after embedding into polymeric matrices was studied by an iodine indicator technique. The permeability of membranes for gases was measured using a semi-open permeation apparatus with a small volume. Helium permeability depended on filler content and increased monotonously with the increasing content of filler. There were, however, significant deviations of the permeability dependences on filler content from shapes predicted by Bruggeman’s model. The qualitative explanation of the data disagreement with the model was proposed based on a stratification of mixed matrix membranes found by SEM.